An old Tibetan variant for the word "fox" - Coblin, W. South (2024)
In his comparative study, Sino-Tibetan: a Conspectus, P. K. Benedict reconstructs for Proto-Tibeto-Burman (PTB) a form *gwa "fox" (1972:34). In Written Tibetan (WT) this proto-form yields the word wa "fox." Benedict observes that in medial position his PTB *-wa- regularly gives Tibetan -o-. It would therefore seem that it is only where *wa appears in absolute initial position in Tibetan that it essentially retains its PTB form. In principle this formulation is reasonable, though one wonders on general phonological grounds why rounding should have failed to take place here